Data-Driven Models of Governance Across Borders: Assessing Participation, Inclusion, and Convergence in the Digital Era - Stevens, Hallam; Arora, Payal; Konig, Rene; Schaefer, Mirko; Pirdmore, Jason (AoIR Selected Papers of Internet Research, 2017)
We have come quite a distance from Chris Anderson’s “end of theory” euphoria for big data at the helm of decision-making for the betterment of society (2008). Today, numerous scholars have critiqued data-centrism in policy-making and practice (for example, boyd and Crawford 2011). Hannah Arendt argues that governance has repeatedly fallen victim to the “utterly irrational confidence in the calculability of reality” (1972). However, we are also witnessing a number of social innovations across the world that are strategically leveraging on digitization to enable a more transparent, inclusive and representative form of political enactment. These social experiments promise to break away from traditional modes of institutional practice and offer instead a more vibrant form of democratic engagement, empowered by the affordances of “datafication.” This panel critically assesses the nature and role of data emerging from new forms of information and communication technologies in the shaping of social order. Each paper in this panel evaluates the particulars of select social innovations posited to strengthen policymaking and citizen activism in the digital era. The papers that make up this panel move beyond polarizing dialectical perspectives by illuminating the ways in which databases have enabled newer forms of mobilization and solidarity but have equally allowed for novel and hitherto unimagined operations of state and corporate power. We aim for a more nuanced and complex understanding of how a multiplicity of social actors come to play in the makings of public service in the big data era. The first paper examines two new models of governance emerging in the Global South – the social credit system in the People’s Republic of China and the biometric identity system in India. Each promises to consolidate public services and citizen identities for social good. The second paper analyzes the opening of government data in Singapore through the website data.gov.sg. It examines the motivations behind such opening of data and assesses the extent to which it enables citizen and civil society action. The third paper examines the emergence of data-driven cities in the Netherlands, comparing Amsterdam, Utrecht, Eindhoven, and Dordrecht. A fourth paper focuses on user experiences in relation to mobile privacy in the United States and the Netherlands. It focuses on everyday negotiations and the participation of citizen/consumers in the production of different forms of data within these two countries. The final paper turns attention to the role of “citizen conferences” in Germany and proposes new approaches to policy-making that emerge from both digital and material engagements. The studies in these papers are situated in diverse models of policy-making, governance, and/or activism across borders. They address the datafication of publics, spaces and social interactions. Thereby, this panel opens up a conversation on global templates of databased governance through the lens of participation, inclusion and convergence. This is occurring within increasingly networked publics, raising questions for instance about privacy in context (see for instance Nissenbaum 2009), divides between digital and material practices or online-offline distinctions, the potentials for urban-digital commons, and the embeddedness of value laden systems, particularly with regard to their enculturation across different (political, social, and economic) contexts. By comparing examples emerging from different national and political circumstances, we hope to illuminate the diverse potentialities and valences of big data. Moreover, these panels examine both top-down and highly centralized efforts to mobilize data, alongside citizen-driven, bottom-up data-collection schemes. By placing these cases side-by-side, we hope to show the vastly divergent possibilities and meanings of data work, as well as suggesting some limitations on data’s democratic potential. References Anderson, Chris (2008). The end of theory: The data deluge makes the scientific method obsolete. Wired, 23 June. https://www.wired.com/2008/06/pb-theory/ Arendt, Hannah (1972). Crises of the Republic. New York: Harcourt Brace Jovanovich. boyd, danah and Kate Crawford (2011). Six provocations for big data. A decade in Internet time: Symposium on the dynamics of Internet and society, 21 September. Available at SSRN: http://dx.doi.org/10.2139/ssrn.1926431 Nissenbaum, H. (2009). Privacy in context: Technology, policy, and the integrity of social life. Stanford University Press.